Influence of 2 '-fucosyllactose and galacto-oligosaccharides on the growth and adhesion of Streptococcus mutans - Salli K; Soderling E; Hirvonen J; Gursoy UK; Ouwehand AC (Cambridge University Press, 2022)
Human milk oligosaccharides, such as 2 '-fucosyllactose (2 '-FL), and galacto-oligosaccharides (GOS), a prebiotic carbohydrate mixture, are being increasingly added to infant formulas, necessitating the understanding of their impact on the oral microbiota. Here, for the first time, the effects of 2 '-FL and GOS on the planktonic growth and adhesion characteristics of the caries-associated oral pathogenStreptococcus mutanswere assessed, and the results were compared against the effects of xylitol, lactose and glucose. There were differences inS. mutansgrowth between 2 '-FL and GOS. None of the threeS. mutansstrains grew with 2 '-FL, while they all grew with GOS as well as lactose and glucose. Xylitol inhibitedS. mutansgrowth. The adhesion ofS. mutansCI 2366 to saliva-coated hydroxyapatite was reduced by 2 '-FL and GOS. Exopolysaccharide-mediated adhesion ofS. mutansDSM 20523 to a glass surface was decreased with 2 '-FL, GOS and lactose, and the adhesion of strain CI 2366 strain was reduced only by GOS. Unlike GOS, 2 '-FL did not support the growth of anyS. mutansstrain. Neither 2 '-FL nor GOS enhanced the adhesive properties of theS. mutansstrains, but they inhibited some of the tested strains. Thus, the cariogenic tendency may vary between infant formulas containing different types of oligosaccharides.